Fracture distribution in a folded fluvial succession: The Puig-reig anticline (south-eastern Pyrenees). (October 2021) - Sun, Xiaolong; Gomez-Rivas, Enrique; Alcalde, Juan; Martín-Martín, Juan Diego; Ma, Cunfei; Muñoz-López, Daniel; Cruset, David; Cantarero, Irene; Griera, Albert; Travé, Anna
Abstract: Sedimentary rocks of foreland fold-and-thrust belts typically undergo intensive fracturing as folds grow. The resulting fracture networks can present significant variations depending on the distribution of sedimentary facies and the complex structural characteristics of fold-and-thrust belts. The Puig-reig anticline, located in the south-eastern Pyrenees, mainly exposes proximal fluvial deposits in the north limb and medial fluvial deposits in the rest of the anticline. Thus, this anticline constitutes an excellent case study to investigate the main controls on the distribution of fracture networks in folded fluvial deposits, in terms of structural position and lithofacies variations. Outcrops were selected to be representative of different structural positions, from the fold hinge to its limbs, and of a variety of the main lithofacies, from proximal to medial fluvial deposits. Fracture data were acquired using the linear scanline method. The results indicate that the anticline rocks have been affected by four sets of fractures. The north limb is dominated by thick conglomerate bodies with interlayered sandstones deposited from unconfined flash floods and wide-shallow channel streams in the proximal fluvial fan, and presents large fracture spacing and low fracture intensity but relatively large fracture length and aperture. The crest and the crest-limb transition zones are mainly characterised by interlayered conglomerates, sandstones, siltstones and clays, deposited from braided channel streams and overbanks in the medial fluvial fan, and present fractures with relatively high fracture intensity and variable fracture length and aperture. The south limb, composed of channel filling sandstone layers and stable overbank fine deposits in the medial fluvial fan, is characterised by low fracture intensity and small fracture length and aperture. Based on multiple linear regression analysis, fracture intensity is mainly controlled by the structural position, bedding thickness and lithological associations, with relatively more intense fracturing in thin sandstone layers with multiple interlayers of fine deposits in the anticline crest. The fracture length mainly depends on bedding thickness and is affected lithological associations. The fracture apertures are mainly controlled by lithofacies, with relatively higher apertures affecting conglomerate bodies. The results of this study are relevant for characterising similar systems in the subsurface, where data is scarce. Highlights: Fracture data is collected from a folded fluvial succession using a linear scanline method. Fracture intensity is significantly controlled by the structural position, bedding thickness and lithological associations. Conglomerates present lower fracture intensity and larger fracture length and aperture than sandstones. Among all the fluvial facies, channel-filling sandstones in high-strain zones present the highest potential to be effective reservoirs.